Precautionary Principle Dalam Kebijakan Kehutanan Riau - Hikmah Bima Oditya; Sri Lestari Rahayu (Faculty of Law Universitas Sebelas Maret, 2018)
This research aims to explore how the precautionary principle should be applied in Riau forestry policy. Since its emergence in Germany in 1971, the precautionary principle holds a central position in the enforcement of the international environmental law. Nowadays, the precautionary principle is widely adopted in the international regulations, for instance: The law of climate change (UNFCCC). Indonesia is one of the countries that ratified the UNFCCC. Therefore, Indonesia has been bound by the obligations related to the substance of the convention. The high intensity of forest and land fires in Indonesia, especially in Riau Province, requires the government evaluated previous commitments and actions through a precautionary approach. The opportunity can be applied to several policy options that can be set forth in the Nationally Determined Contribution (NDC) in the Paris Agreement 2015 regime which will be discussed later in this article.